Extracts from Quercus sp. acorns exhibit in vitro neuroprotective features through inhibition of cholinesterase and protection of the human dopaminergic cell line SH-SY5Y from hydrogen peroxide-induced cytotoxicity - Custódio, Luísa; Patarra, João; Alberício, Fernando; Neng, Nuno Rosa; Nogueira, José Manuel Florêncio; Romano, Anabela (Industrial Crops and Products, 2013)
In this work non polar (hexane) and polar (methanol and hot water) extracts of cork oak (Quercus suber) and holm oak (Quercus ilex) acorns were evaluated for the first time for in vitro neuroprotective properties, by determining their in vitro inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) and their capacity to attenuate hydrogen peroxide-induced injury in the human dopaminergic cell line SH-SY5Y. Total content of phenolics, tannins and flavonoids, HPLC profile of the main phenolic compounds and antioxidant activity were also determined. The methanol extracts showed inhibitory activities against AChE and BChE. The best results toward AChE were obtained with cork oak extract (69.4% inhibition at the concentration of 1 mg/ml), while for BChE the highest inhibition (46% inhibition at the concentration of 1 mg/ml) was obtained with holm oak. Moreover, methanol extracts were able to prevent oxidative stress-induced cytotoxicity in SH-S5SY cells. The methanol extract of holm oak exhibited the highest RSA, with values of 63.8% and 49.7% on DPPH and ABTS radicals at the concentration of 1 mg/ml, respectively. In general the extracts exhibited no reducing potential. The methanol extract from cork oak acorns had the highest content in phenolic compounds (25.2 mg GAE/g, DW), while the water extracts had the maximum level of flavonoids (1.7 mg RE/g, DW). Tannins were present in higher amounts in the water extract of holm oak (91.6 CE/g, DW). The main compounds in the methanol extract from holm oak acorns were (−)-epicatechin and catechol, while gallic acid and (+)-catechin were the main constituents of the methanol extract from cork oak acorns. Our results indicate that cork and holm oak acorns provide a valuable source of biomolecules useful for alleviating symptoms associated with Alzheimer's disease and other neurodegenerative ailments.
Keywords: acorns; Alzheimer's; Cholinesterase; Dementia; Mediterranean trees; Neurological disorders

Seasonal and inter-annual variations of gas exchange in thirteen woody species along a climatic gradient in the Mediterranean island of Mallorca - Gulías, J.; Cifre, J.; Jonasson, S.; Medrano, H.; Flexas, J. (Flora - Morphology, Distribution, Functional Ecology of Plants, 2009)
We studied the inﬂuence of summer drought and winter temperatures on seasonal and spatial variations of lightsaturated net photosynthesis and stomatal conductance in Mediterranean woody species. We measured variations in leaf gas exchange over 3 years in 13 Mediterranean trees and shrubs, located at four different sites along a climate gradient of temperature and precipitation in the island of Mallorca (West Mediterranean basin). Net photosynthesis and stomatal conductance were at a maximum during spring, autumn or winter and at a minimum during summer in most sites, species and years. Nevertheless, important spatial, temporal and species-speciﬁc variations were observed. Summer drought limitation to gas exchange was greatest in the dry part of the transect, where many species showed their maximum gas exchange rate during winter. In contrast, winter temperatures limited gas exchange of many species at the wet and cool end of the transect, while summer depression of gas exchange was shorter and less pronounced. These results suggest that the effect on carbon ﬁxation and productivity by the predicted future increase of aridity in the Mediterranean basin will depend on whether gas exchange is mostly limited by summer drought or by low winter temperatures.
Keywords: evergreen sclerophyllous species; Mediterranean shrubs; Mediterranean trees; photosynthesis; summer drought

Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity - Gullo, M A Lo; Salleo, S; Rosso, R; Trifilo, P (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.
Keywords: cavitation; Drought resistance; hydraulics; Mediterranean trees; Reforestation; water relations

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; INNES, JOHN L. (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; Innes, John L (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress